Estimation of Shelf Life with Respect to Bacillus cereus Growth in Tteokgalbi at Various Temperatures Using Predictive Models. Issue 4 (14th June 2014) - Heo, Chan; Kim, Hyun Wook; Ko, Kyung Yuk; Kim, Kee‐Tae; Paik, Hyun‐Dong
Abstract Predictive models to describe the growth of Bacillus cereus in tteokgalbi were developed during storage under various temperatures (5–25C) and inoculation levels (2 and 3 log) to estimate the shelf life. To develop primary models, the observed data were applied to the Baranyi and Gompertz equations. The growth rate was dependent on temperature, but the effect of inoculation level on growth rate was not significant (P > 0.05). Thus, the secondary polynomial model was developed as a function of temperature. At 5C, the predicted shelf life of tteokgalbi was approximately 65.5–73.2 h. The shelf life at 15 or 25C decreased sharply during storage, and was less than 20 h during storage. All primary and polynomial secondary models were characterized by high R2 values, small root mean square error values and very ideal values of Bf and Af. These results present reliable predictive growth models describing the growth of B. cereus under various temperature conditions in tteokgalbi. Practical Applications Many traditional homemade foods have been industrialized at recent days. Tteokgalbi is the most popular processed pork product in Korea, and the acceptability of consumers is high because of its good flavor and nutritional value. During industrial production, the possibility of contamination of pathogens including Bacillus cereus can be high through manufacture and distribution. The predictive model in this study can be used to control the possibility of contamination for safety of tteokgalbi as basic information.